Socially responsible HR practices and their effects on employees' wellbeing: Empirical evidence from Catalonia, Spain - Dolors Celma; Esther Martinez-Garcia; Josep M. Raya (European Research on Management and Business Economics (ERMBE), 2018)
Corporate social responsibility towards employees has been promoted by international organizations that produced recommendations, conventions, principles and other documents to enhance job quality and wellbeing at work. However, much is still unknown about their effects. This article empirically analyses the effectiveness of several practices of human resource management, which are “responsible” according to those international institutions, in relation to three well-known dimensions of employees' wellbeing at work: job stress, job satisfaction and trust in management. The empirical analysis is conducted for the case of Catalonia using information from the Quality of Work Life Survey for 2007. The results show that, in general, higher job quality increases employees' wellbeing at work, but some practices are more effective than others for each specific wellbeing dimension. It is also noteworthy that some practices, such as job security and good environmental working conditions, seem to positively affect all domains of employees' wellbeing at work.
Keywords: J28; M14; M54; 650; Corporate social responsibility; Human resource management; Employee's wellbeing